2011
DOI: 10.1371/journal.pone.0026275
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Plants and Enemy Release: Evolution of Trait Means and Trait Correlations in Ulex europaeus

Abstract: Several hypotheses that attempt to explain invasive processes are based on the fact that plants have been introduced without their natural enemies. Among them, the EICA (Evolution of Increased Competitive Ability) hypothesis is the most influential. It states that, due to enemy release, exotic plants evolve a shift in resource allocation from defence to reproduction or growth. In the native range of the invasive species Ulex europaeus, traits involved in reproduction and growth have been shown to be highly var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
2

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(54 citation statements)
references
References 61 publications
2
50
2
Order By: Relevance
“…While further experiments would be necessary to precisely identify all of the cues involved, our results show that E. ulicis females use both internal and external cues in their oviposition choice, and that response to at least some of these cues is adaptive. However, the preferences observed here on isolated pods were different from those observed on isolated flowers, and did not explain the whole-plant infestation rate in the common garden [27]. Together with previous studies, these results reveal that the foraging behaviour of E. ulicis weevils requires the capacity to respond to a wide variety of cues: whole-plant traits [21], flower traits, internal and external pod cues (this study), and cues indicating the presence of conspecifics [26] or the presence of the competitor Cydia succedana [19].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…While further experiments would be necessary to precisely identify all of the cues involved, our results show that E. ulicis females use both internal and external cues in their oviposition choice, and that response to at least some of these cues is adaptive. However, the preferences observed here on isolated pods were different from those observed on isolated flowers, and did not explain the whole-plant infestation rate in the common garden [27]. Together with previous studies, these results reveal that the foraging behaviour of E. ulicis weevils requires the capacity to respond to a wide variety of cues: whole-plant traits [21], flower traits, internal and external pod cues (this study), and cues indicating the presence of conspecifics [26] or the presence of the competitor Cydia succedana [19].…”
Section: Discussioncontrasting
confidence: 91%
“…To focus on pod and flower cues and avoid the confounding effects of whole-plant traits such as pod and flower density or plant size [22], we worked on fresh isolated pods and flowers that were collected just before the experiments in the common garden described by Hornoy et al [27]. In this garden, located in Rennes (Brittany, France), gorse plants from seeds collected in Brittany and Scotland (native range), and Reunion and New Zealand (invaded range) have been grown in a randomized pattern since October 2006.…”
Section: Study Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Population names were encoded with the first letters representing the region it comes from: SPA for Spain, FRA for France, SCO for Scotland, CHI for Chile, NZE for New Zealand, REU for Reunion, and USA for California, USA. Populations FRA1, FRA2 and FRA3 correspond to populations BCC, BCV and BKE, respectively, in Hornoy et al (2011Hornoy et al ( , 2012; SCO1, SCO2, SCO3 correspond to SBA, SCR, SST; REU1, REU2, REU3 correspond to RLB, RMA, RPB; and NZE1, NZE2, NZE3 correspond to ZAU, ZCH, ZWE, respectively.…”
Section: Population Samplingmentioning
confidence: 99%
“…Also, very low cytoplasmic diversity has been found in the Ulex genus (Cubas et al, 2005;Kader Ainouche, personal communication). However, it has been shown that the phenotypic diversity is great, both in the native range and in the invaded regions (Hill et al, 1991;Tarayre et al, 2007;Hornoy et al, 2011), and that it has a genetic basis (Atlan et al, 2010). The study of genetic diversity in allopolyploids like U. europaeus has now become possible using methods recently developed for nuclear markers, such as allozymes or microsatellites (Obbard et al, 2006;Falush et al, 2007).…”
Section: Introductionmentioning
confidence: 99%